(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The purpose of this paper is to provide an overview of the historical framework of Human-Computer Interaction (HCI). The overview emphasises the historical achievements in the field of research while highlighting the relevance of HCI, its beginnings, and its growth on a global scale. In addition, the review focuses on the reasons why the subject of HCI emerged in India. It also covers the fundamentals of HCI, usability, and other related terms. The method used for this review article is based on literature search of journal articles, books, conference proceedings, websites, and online news related to the listed keywords. Given that HCI is becoming more and more integrated into our daily lives, it may be said that it will also be responsible for defining the future. It can be difficult for some users to imagine living without their devices because they have become an integral part of contemporary society.